2017
DOI: 10.1016/j.biopsycho.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Association of posterior EEG alpha with prioritization of religion or spirituality: A replication and extension at 20-year follow-up

Abstract: A prior report (Tenke et al. 2013 Biol. Psychol. 94:426–432) found that participants who rated religion or spirituality (R/S) highly important had greater posterior alpha after 10 years compared to those who did not. Participants who subsequently lowered their rating also had prominent alpha, while those who increased their rating did not. Here we report EEG findings 20 years after initial assessment. Clinical evaluations and R/S ratings were obtained from 73 (52 new) participants in a longitudinal study of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 50 publications
4
53
0
8
Order By: Relevance
“…As we had previously reported cortical thinning in these regions as a stable biomarker for depression risk (Hao et al, ; Peterson et al, ), we hypothesized that the thicker cortices in those reporting high importance of R/S beliefs may serve as a compensatory or protective mechanism. In subsequent studies on the same participants, we found increased default mode network (DMN) connectivity (Posner et al, ), and greater EEG alpha among individuals at high (compared to low) familial risk for depression (Tenke et al, ). However, within the subgroup of individuals at high risk for depression, those reporting that R/S was highly important to them had reduced DMN connectivity (Svob, Wang, Weissman, Wickramaratne, & Posner, ) and greater EEG alpha (Tenke et al, ).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…As we had previously reported cortical thinning in these regions as a stable biomarker for depression risk (Hao et al, ; Peterson et al, ), we hypothesized that the thicker cortices in those reporting high importance of R/S beliefs may serve as a compensatory or protective mechanism. In subsequent studies on the same participants, we found increased default mode network (DMN) connectivity (Posner et al, ), and greater EEG alpha among individuals at high (compared to low) familial risk for depression (Tenke et al, ). However, within the subgroup of individuals at high risk for depression, those reporting that R/S was highly important to them had reduced DMN connectivity (Svob, Wang, Weissman, Wickramaratne, & Posner, ) and greater EEG alpha (Tenke et al, ).…”
Section: Introductionmentioning
confidence: 83%
“…In subsequent studies on the same participants, we found increased default mode network (DMN) connectivity (Posner et al, ), and greater EEG alpha among individuals at high (compared to low) familial risk for depression (Tenke et al, ). However, within the subgroup of individuals at high risk for depression, those reporting that R/S was highly important to them had reduced DMN connectivity (Svob, Wang, Weissman, Wickramaratne, & Posner, ) and greater EEG alpha (Tenke et al, ). In other words, brain differences associated with importance of R/S beliefs were the opposite of those associated with disease risk, suggesting that R/S may provide a compensatory mechanism or buffering effect.…”
Section: Introductionmentioning
confidence: 83%
“…Solutions for amplitude spectra (rather than power or log power) appeared optimal, and the authors argued for the application of CSD transformations to provide a better model of the underlying brain activity. This CSD/f‐PCA approach has since been applied in relation to the treatment of depression (Tenke et al, ), and further research employing this f‐PCA methodology has also been published (e.g., Kayser et al, ; Tenke, Kayser, Abraham, Alvarenga, & Bruder, ; Tenke, Kayser, Pechtel et al, ; Tenke, Kayser, Svob et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Except for the three electrodes PO4, PO6, and OZ on the outer boundary of the posterior brain region, all other 11 electrodes jointly are shown to have played a significantly important role in predicting SSRI response, and such effects concentrate on the overlapping frequency range between theta and alpha bands (around 7 Hz) through most of the alpha frequency range. These results corroborate previous findings that baseline CSD measures at alpha or/and theta frequency bands are viable predictors of clinical response to SSRIs (eg, Tenke et al ., ).…”
Section: Application To Predict Antidepressant Response Using Eeg Datamentioning
confidence: 97%